DETERMINAN FAKTOR RISIKO STUNTING PADA BALITA DETERMINANTS OF STUNTING RISK FACTORS IN TODDLERS - Sulastry Pakpahan; Elly Sianturi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Stunting is a nutritional problem characterized by chronic growth and development disorders in children, has an impact on the physical (short/dwarf stature), and interferes with brain development, affecting children's abilities and achievements, productivity, and creativity. Based on SSGI data for 2021 in North Tapanuli Regency, the percentage of stunting is around 26.7% of the number of children under five. This figure is still below the national stunting rate target of below 24%. The purpose of this study was to determine the risk factors associated with stunting. This analytic cross-sectional study was conducted from February to April 2022. The sample in this study consisted of 96 toddlers divided into 2 groups, namely the toddler group with stunting of 48 people and the group of toddlers with normal nutritional status of 48 people. Sampling was taken by purposive sampling, namely those who came to be brought by their mothers to monitor growth and development at posyandu in the North Tapanuli Regency area. The inclusion criteria were toddlers aged 24-59 months, domiciled in North Tapanuli Regency, lived with their parents, and had a mother and child health record book (KIA). Data were obtained using questionnaires, and the MCH handbook and based on the results of anthropometric examinations. Based on the results of logistic regression, it showed that the most dominant risk factor was a history of chronic infection in toddlers with stunting (OR=24.8; 95% CI 4.43 - 140.11; p<0.000), mother's knowledge (OR=18.2; 95%CI 3.62 – 91.24;p<0.000), history of exclusive breastfeeding (OR=10.7; 95%CI 2.15 – 53.92;p<0.004) and maternal weight during pregnancy (OR = 8.1; 95% CI 1.62 – 40.36; p <0.01). It is hoped that the active participation of the family, especially mothers of toddlers, will prevent stunting by fulfilling nutrition during pregnancy and nutrition for toddlers, preventing chronic infections, and provide exclusive breastfeeding.